'They can't fool me, but they can fool the others!' Third person effect and fake news detection. (April 2020) - Corbu, Nicoleta; Oprea, Denisa-Adriana; Negrea-Busuioc, Elena; Radu, Loredana
The aftermath of the 2016 US Presidential Elections and the Brexit campaign in Europe have opened the floor to heated debates about fake news and the dangers that these phenomena pose to elections and to democracy, in general. Despite a growing body of scholarly literature on fake news and its close relatives misinformation, disinformation or, more encompassing, communication and information disorders, few studies have so far attempted to empirically account for the effects that fake news might have, especially with respect to what communication scholars call the third person effect. This study aims to provide empirical evidence for the third person effect in the case of people's self-perceived ability to detect fake news and of their perception of others' ability to detect it. Based on a survey run in August 2018 and comprising a national, diverse sample of Romanian adults ( N  = 813), this research reveals that there is a significant third person effect regarding people's self-reported ability to spot fake news and that this effect is stronger when people compare their fake news detection literacy to that of distant others than to that close others. Furthermore, this study shows that the most important predictors of third person effect related to fake news detection are education, income, interest in politics, Facebook dependency and confirmation bias, with age being a non-significant predictor.